Development Of Web Application To Manage School Student And Finance Data (A Case Study in MIM Gonilan, Kartasura) - FAUZI, Kemal (2015)
Information and computer technology advances very rapidly inline with the increase of the need for information. The use of IT in education has also become the norm. As for Elementary School MIM Innovative Gonilan, information systems have an important role in an educational institutions to improve the effectiveness and performance. Managing student and finance data is a very important part because every activity in school will definitely require funding. The system design is intended to process and managing student financial data. The main purpose of developing financial information system is for processing financial data quickly and accurately, because manual system that is currently used cause some problems, the current system does not produce 100% accurate data and data processing system of financial administration manual also requires a long time. Based on the analysis of the problem we try to design a student and financial information system that is expected to support the reporting of financial data so that reports generated more quickly and accurately. The system was implemented using PHP programming language and MySQL database. The results is a functioning financial information system for processing and making financial reports, and the financial data processing becomes more accurate, faster, and more timely than manual processing.